Analysis of Financial Inclusion and Technology about Implementation of Coastal MSMEs in Sumenep, Madura - Purnomo, Arie Setyo Dwi; Kurriwati, Nirma (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The goal of this study is to test aspects of financial inclusion and technology side on MSME implementation in Madura. This study was conducted in Sumenep with the object of research being the MSME sector in Pesisir Sumenep. The collection data method is done by spreading questionnaires and observations. Data compilation using regression analysis techniques to test the hypothesis. According to research results, the financial inclusion and technology variables have a positive and significant impact on the performance of SMEs in Sumenep Coast, Madura. Financial inclusion and technology have great potential to drive inclusive and sustainable economic growth through expanding access to financial services and technology for MSMEs, which can reduce inequality and encourage innovation, so the government has to continue to support development infrastructure for financial inclusion and technology for MSMEs.